2015
DOI: 10.1021/acs.chemmater.5b03147
|View full text |Cite
|
Sign up to set email alerts
|

Crystal and Electronic Structures of Complex Bismuth Iodides A3Bi2I9 (A = K, Rb, Cs) Related to Perovskite: Aiding the Rational Design of Photovoltaics

Abstract: Ternary bismuth halides form an interesting functional materials class in the context of the closely related Pb halide perovskite photovoltaics, especially given the significantly reduced toxicity of Bi when compared with Pb. The compounds A 3 Bi 2 I 9 (A = K, Rb, Cs) examined here crystallize in two different structure types: the layered defectperovskite K 3 Bi 2 I 9 type, and the Cs 3 Cr 2 Cl 9 type. The latter structure type features isolated Bi 2 I 9 3− anions. Here, the crystal structures of the ternary i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

46
512
0
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 444 publications
(564 citation statements)
references
References 82 publications
46
512
0
6
Order By: Relevance
“…These include the valence and conduction band onsets with respect to the Fermi level, as well as the vacuum level position. 19,27,162 Photoemission spectroscopy is a powerful tool to investigate the band structure of novel semiconductor materials and the position of the Fermi level in the bandgap. The techniques are applicable not only to thin films, 163 but also single crystals, for which band positions need to be precisely known for electrical characterization and device applications.…”
Section: Atom Probe Tomography (Apt)mentioning
confidence: 99%
See 1 more Smart Citation
“…These include the valence and conduction band onsets with respect to the Fermi level, as well as the vacuum level position. 19,27,162 Photoemission spectroscopy is a powerful tool to investigate the band structure of novel semiconductor materials and the position of the Fermi level in the bandgap. The techniques are applicable not only to thin films, 163 but also single crystals, for which band positions need to be precisely known for electrical characterization and device applications.…”
Section: Atom Probe Tomography (Apt)mentioning
confidence: 99%
“…In particular, inaccuracies may arise from this method if the density of states at the leading edge is low and there is no distinct tangent to take, as occurs for many PIMs reported. 19,27,30,163 A method to visualize gap states is to plot the leading edge on a semilogarithmic scale, since band tails can be described by exponential functions. 172,173 This is illustrated in Figure 6a for organic small molecules.…”
Section: Fitting the Leading Edge In Photoemission Spectroscopy Measumentioning
confidence: 99%
“…[5,9,[11][12][13] Timecorrelated single photon counting (TCSPC) measurements of (CH 3 NH 3 ) 3 Bi 2 I 9 and Cs 2 AgBiBr 6 , among others, have shown that these materials exhibit lifetimes exceeding 1 ns. [11,15,16] This is significant because analysis of established thin-film solar absorbers has shown that materials with minority-carrier lifetimes of 1 ns or above have the potential to reach or exceed 10% efficiency.…”
mentioning
confidence: 99%
“…[17] Many of these bismuth halides and chalcohalides have also demonstrated improved air-stability compared to hybrid lead-halide perovskites. [11,13,15] However, devices based on these materials have low reported power conversion efficiencies under AM 1.5G illumination, between 0.1 and 1.2%. [1] The short-circuit current densities (J SC , <4 mA cm −2 ) and external quantum efficiencies (EQEs, <60%) have also been poor, [1,18] in spite of efforts to extend the photoconversion range of bismuth halide semiconductors (J SC < 3.4 mA cm −2 , EQE < 25%).…”
mentioning
confidence: 99%
“…High Born effective charges have been calculated in bismuth-based compounds. 22 The compounds also have high calculated ionic (or static) dielectric constants (Table I). The partial density of states for three such compounds are shown in Fig.…”
Section: Theoretical Insightsmentioning
confidence: 99%